B422 A comparison of spinal anesthesia characteristics between hyperbaric ropivacaine and hyperbaric bupivacaine in subarachnoid block for lower segment caesarean section: a prospective randomised study. (11th August 2022) - Joshi, R; Latha, N; Ramesh, J; Yachendra, G; Jeevan, R
Abstract : Background and Aims: Ropivacaine is suggested to have an improved safety profile over bupivacaine in terms of cardiotoxity and CNS toxicity. We aimed to study the spinal block characteristics and hemodynamics between commercially available preparation of 0.75% hyperbaric ropivacaine and 0.5% hyperbaric bupivacaine in caesarean section. Methods: This prospective, randomized, double-blinded study was approved by the Institute ethics committee. Following exclusion, 64 term parturients were randomised to receive 0.75% hyperbaric ropivacaine 2 ml (15mg) (commercially available Ropin Heavy, Neon) or 0.5% hyperbaric bupivacaine 2 ml (10mg) (commercially available Anawin Heavy, Neon), with additive fentanyl 10 micrograms in both groups.Our primary objective was to evaluate duration of sensory blockade. Secondary objectives were to compare the hemodynamics and vasopressor usage, onset of sensory and motor blockade, duration of motor blockade, quality of anesthesia, complications and APGAR score. Results: Two segment sensory regression and motor blockade regression was faster in ropivacaine than bupivacaine (p=0.0005, 0.0005). The onset of sensory block to T6 and T4 and complete motor block was slower in ropivacaine (p= 0.02, 0.07, 0.0005 respectively). The mean arterial pressure was significantly higher throughout all time intervals in ropivacaine than bupivacaine and vasopressor usage was lesser in Ropivacaine. The intraoperative quality of anesthesia was adequate in both groups. The APGAR scores remained high and side effects did not differ between groups. Conclusions: 0.75% Ropivacaine can be a suitable alternative to 0.5% Bupivacaine in patients undergoing caesarean section under spinal anaesthesia with a benefit of early sensory and motor recovery, and better intraoperative hemodynamic profile without significant adverse effects.